Hands-on Sencha Touch 2 A Real-World App Approach - Boonstra, Lee (O'Reilly Media, 2014)
Sencha Touch 2.1 offers mobile developers a smooth and convenient toolkit for building complex but snappy web applications. This Cookbook gives readers experience building a complete application, combining all the fundamental components of Sencha Touch, including Sencha Cmd, Sencha's MVC and Component tools, form handling and styling, integration with outside data, support for multiple devices, and distribution through app stores.